Risk factors and prevalence of periodontitis in communitydwelling elders in Mexico - S. Aı´da Borges-Ya´n˜ ez (journal of clinical periodontology, 2006)
Aim: The objective of this study was to determine whether an association existed between chronic systemic diseases/conditions, risk factors common in old age, and the extent and severity of chronic periodontal disease. Materials and Methods: Sociodemographic and lifestyle characteristics were examined by contrasting rural, urban-marginal, and urban social environments in Central Mexico. Data were analysed with Analysis of Variance, w2 tests, and multivariable logistic regression. Results: A total of 473 adults 60 years old and over were interviewed; 315 were also examined and underwent laboratory assays (participation rate, 66%); women, 62%; mean age 73 8 years; 23% edentulous. The distribution of periodontitis by sociodemographic variables showed differences across locales (73% low-urban, 57% middle-urban, 29% rural). The regression model indicated that periodontitis was more frequently associated with low-urban locale, higher systolic blood pressure, higher body mass index, and worse calculus readings, with an interaction whereby being obese and having a high calculus index was associated with a high probability of having periodontitis. Conclusions: Overall periodontal conditions were fair. While we identified oral, systemic, and social variables that modulated the experience of periodontitis, it would appear that urban, low social class elders appeared to have worse periodontal conditions.